Reflexões sobre o Humanismo Medieval a partir da correspondência de Abelardo e Heloísa - Kelly Cristiane Mendes Alves (Universidade Federal do Amazonas, 2016)
Humanism is commonly understood as the historical period comprising the 15th and 16th centuries. One can, however, affirm the existence of a humanism in the Middle Ages that is typically moral humanism, which led Christian thinkers to consult the Ancients to understand what man is. The medievals needed them, and especially because, as Christians, they placed the concern around salvation at the center of everything and they lacked the knowledge of this nature that they needed to save. Thus, the Correspondence of Abelardo and Heloísa offers unique elements for an accurate understanding of this theme. In these letters, more than merely presenting the love of lovers, a discussion takes place through which one can glimpse an image of what medieval humanism is as they present human vices and virtues through philosophical categories from antiquity.